The Effect of Food Quality, Social Media Marketing and Brand Awareness on Consumer Repurchase Interest in Mama Bread - Piter, Jessica; Soediro, Moses; Yuwono, Victor Kurniawan; Irtanto, Devina; Grasielda, Ivana (JURNAL ILMIAH EDUNOMIKA, 2025)
One of the businesses that has begun to utilize social media in buying and selling activities is the culinary industry. Mama Bread is a business engaged in the food and beverages sector, specifically a homemade-based bakery established in 2010 and located in Lombok. Mama Bread faces an issue related to consumer repurchase intention, as the business tends to be unable to attract previous customers to make repeat purchases. Based on a preliminary survey conducted by the researcher, problems were found in food quality, social media marketing, and brand awareness. The purpose of this study is to determine the effect of food quality on consumer repurchase intention at Mama Bread, the effect of social media marketing on consumer repurchase intention at Mama Bread, and the effect of brand awareness on consumer repurchase intention at Mama Bread. This study involved a total sample of 150 Mama Bread consumers. The research method used is quantitative, with multiple linear regression analysis using the Statistical Product and Service Solution (SPSS). The results of this study indicate that food quality, social media marketing, and brand awareness have a positive and significant effect on consumer repurchase intention at Mama Bread.